The prevalence of practicing breast self-examination and knowledge of breast cancer disease among women attending secondary health facility - Olaogun, Julius Gbenga; Emmanuel, Eyitayo Ebenezer; Dada, Samuel Ayokunle; Odesanmi, Olakunle Muyiwa; Adesua, Oladapo Atolagbe (International Surgery Journal, 2017)
Background: Early diagnosis has been shown to improve the prognosis of breast cancer, hence breast self-examination (BSE) as a screening method may have its benefits. The aim of the present study is to determine the prevalence of BSE practice, the correctness of the practice steps and the knowledge of breast cancer disease among women attending secondary health facility. Methods: The study was a descriptive study among women attending antenatal care and immunization clinics at State Specialist Hospital, Ikere-Ekiti between October and December 2015. A total of 238 women seen during the period and who consented to participate in the study were included. Structured self-administered questionnaire was used and data obtained was analyzed using SPSS version 20. Level of significance was set at P<0.05. Results: Of 238 respondents, 94.2% were between 20 and 39 years and mostly married (86.1%). Overall, 56.7% were aware of BSE mainly through health workers (44.4%) and information media (30.4%). A little above half (55.6%) practiced BSE and 24% could be adjudged to have good practice. Performing BSE was significantly related to respondents’ level of education (p=0.001) and marital status (p=0.032). There was high awareness (84%) of breast cancer but the vast majority (87%) had poor knowledge of breast cancer symptoms and signs. Conclusions: This study revealed poor quality of BSE practice and poor knowledge of breast cancer symptoms among our women despite good awareness. There is need for more health education to improve the quality of BSE practice and knowledge of breast cancer disease for early detection and treatment.